Effects of degradable films with different degradation cycles on soil temperature, moisture and maize yield - Shen, Lixia; Zhang, Yumeng; Lan, Yinchao; Li, Ruofan (International Journal of Agricultural and Biological Engineering, 2019)
Photo biodegradable film is an ideal degradable mulch film with synergistic effect of photo-degradability and biodegradability. To examine the covering effects of different films, maize was cultivated in the field with three kinds of degradable films (DF) mulching which had different degradation cycles (DF No. 1, No. 2 and No. 3), with common plastic film mulching and no filming mulching (open ground) as comparison. The degradation rates and degrees of degradable films were examined, and the effects of different films on soil temperature, soil moisture, maize yield and relevant characteristics in each treatment were analyzed. The results indicated that the degradable films had good degradability, and the weight loss rate in 100 d for DF No.1, No.2, and No.3 were 22.31%, 19.46%, and 15.63%, which were 4.16, 3.63, and 2.92 times of the plastic film, respectively. In the early period of maize growth, the degradable films had good warming effects on soil, which were similar with the plastic film. The effect of DF No.2 on soil water conservation was slightly better than that of DF No.1 or No.3, similar with that of the plastic film. The soil water contents in 0-140 cm depths were significantly higher for DF No.2 than that for the open ground (p < 0.05). The degradable films could significantly promote the ear development of maize, improve the ear characteristics, shorten the bald tip, and increase kernel number per plant (KNP) and 1000-kernel weight (TKW). The grain yields (GYs) for DF No.2, No.1, and No.3 were significantly improved, with 35.15%, 31.35%, and 30.07% higher than that the open ground respectively (p < 0.05). With no significant difference between DF and the plastic film, the GY was increased more for DF No.2 than that for DF No.1 and No.3. The degradable films fulfilled successfully all the functions of the plastic film, thus they were recommended as viable option to the plastic film due to their good degradability.Keywords: degradable film, photo biodegradable film, soil temperature, soil moisture, maize, yieldDOI: 10.25165/j.ijabe.20191203.4065Citation: Shen L X, Zhang Y M , Lan Y C, Li R F. Effects of degradable films with different degradation cycles on soil temperature, moisture and maize yield. Int J Agric & Biol Eng, 2019; 12(3): 36–44.